Aggressive Behavior of Students in Serbia - Jevtić, Bisera (Pedagogika, 2015)
Aggressive behavior is a complex phenomenon that attracts attention because of it’s reinforced in the modern world, and whose long-term study didn’t give any permanent solution to combat this, certainly undesirable behaviors. The reason for the study of aggressive behavior in primary schools is that the school as an institution, which are traditionally considered safe place of children today become a place where more and more present increased aggressiveness students. School climate, school organization and it’s work can pose to students as a protective factor, and so disturbing factor and cause behavioral problems in students. At school there are many different social situations and contacts, some of which are risk factors for the emergence and expression of aggressive student behavior. Therefore, we need to determine what are the situations in the everyday school, which can be a potential source of aggression. The goal of our research is to determine what the type of aggressive behavior are represented in the school and to determine which school situations lead to the manifestation of aggressive behavior in students. Levels of aggression among older elementary and high school students is extremely high, with all the dramatic consequences, even though research shows that aggression and violence by the age groups of students in Serbia is below the average of other countries.